If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5(3x + -12) = 156 Reorder the terms: 3x + -5(-12 + 3x) = 156 3x + (-12 * -5 + 3x * -5) = 156 3x + (60 + -15x) = 156 Reorder the terms: 60 + 3x + -15x = 156 Combine like terms: 3x + -15x = -12x 60 + -12x = 156 Solving 60 + -12x = 156 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -12x = 156 + -60 Combine like terms: 60 + -60 = 0 0 + -12x = 156 + -60 -12x = 156 + -60 Combine like terms: 156 + -60 = 96 -12x = 96 Divide each side by '-12'. x = -8 Simplifying x = -8
| 10×1/8= | | 10×1/8 | | 8sin(2x)-sin(4x)=0 | | ln(9x)+ln(4x)=5 | | 67.3=3.2q | | 188=4x+5(2x+4) | | y=3/2x-4/9 | | 4x-15x=66 | | 160=3x+7(4x-17) | | 3(3x+5)=36 | | 6x+2(6x-7)=76 | | 3a-2=5a | | (3x^2)+4=-5x+5 | | -10=6x+2(-x+13) | | 4m^2+17m+15=0 | | 32y^5+4y^3=0 | | (3x^2-4x)(2x^3+3x-1)=0 | | 2x-2(7x-2)=64 | | -(x-7)=5+2(x-1) | | 18m+5=13m+5 | | 1.08(1.21)(8-x)=10 | | x^2+4-9=0 | | 18c+7=6c-77 | | a+5=-24 | | ln(2x+2)=2.5 | | 7x+4(4x-14)=59 | | 5b=4b-9 | | 110=5x+2(-7+10) | | 12(v+4)-4v=4(2v+4)-22 | | -p/3=4 | | 2sin^2x+sinx+1=0 | | b=4b-9 |